Oconaluftee : The History of a Smoky Mountain Valley - Giddens, Elizabeth (Book collections on Project MUSE., 2023)
"The Oconaluftee Valley, located on the North Carolina side of the Smokies, is home of the Eastern Band of the Cherokee Indians and part of the Great Smoky Mountains National Park (a UNESCO World Heritage Site). This seemingly isolated valley has an epic tale to tell. Elizabeth Giddens offers a deeply researched and elegantly written account of Oconaluftee and its people from Indigenous settlements to the establishment of the national park by Franklin Delano Roosevelt in 1940. She builds the tale from archives, census records, property records, personal memoirs, and more, showing how national events affected all Oconaluftee's people-Indigenous, Black, and white"--